Alkaline Phosphatase: Discovery and Naming of Our Favorite Enzyme. (14th August 2017) - Siller, Alejandro F; Whyte, Michael P
ABSTRACT: Alkaline phosphatase can be considered "our favorite enzyme" for reasons apparent to those who diagnose and treat metabolic bone diseases or who study skeletal biology. Few might know, however, that alkaline phosphatase likely represents the most frequently assayed enzyme in all of medicine. Elevated activity in the circulation is universally recognized as a marker for skeletal or hepatobiliary disease. Nevertheless, the assay conditions in many ways are nonphysiological. The term alkaline phosphatase emerged when it became necessary to distinguish "bone phosphatase" from the phosphatase in the prostate that features an acidic pH optimum. Beginning in 1948, studies of the inborn‐error‐of‐metabolism hypophosphatasia would identify the natural substrates and establish the physiological role of alkaline phosphatase, including in biomineralization. Here, we recount the discovery in 1923 and then eventual naming of this enzyme that remains paramount in our field. © 2017 American Society for Bone and Mineral Research.